(untitled) (Economic and Political Thought, 2024)
The immediate aftermath of the Second World War in Europe was marked by the displacement of millions of national groups in Central and Eastern Europe across newly erected borders. These population movements altered the physical environment and ethnic composition of the region. This article looks at one of these transfers in Poland’s „Recovered Territories” gained from Germany through post‑war peace conferences, and its effect on the region’s cities. The article’s specific focus is how displacement affected the medium‑sized Lower Silesian town of Zielona Góra. The article looks at how the Polish state and individual settlers in Zielona Góra claimed urban spaces as their own whilst simultaneously eradicating signs of their former German inhabitants. Using newly opened archives and drawing on interviews conducted with displaced Poles it shows the development of nationalist and nationalising narratives in the city and the problems the state had in implementing its visions there.